Government Intervention and Suburban Sprawl : The Case for Market Urbanism - Lewyn, Michael (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This book shows how suburban sprawl is at least partially a consequence of government spending and regulation, and suggests anti-sprawl policies that can make government smaller and/or less intrusive. Thus, the book responds to the widely held view that automobile-dependent suburban development (also known as "suburban sprawl") is a natural result of the free market and of affluence, and accordingly cannot be altered without massive government regulation. Michael Lewyn is Associate Professor at Touro Law Center in Central Islip, New York, where he teaches property, land use, environmental law and other courses. He has published over four dozen scholarly articles, and blogs regularly at planetizen.com and marketurbanism.com. .